Analysis of Water Quality of the Meghna River Using Multivariate Analyses and Rpi - Bhuyan, Md Simul; Bakar, Muhammad Abu; Akhtar, Aysha; Hossain, M Belal; Islam, Md Shafiqul (Journal of the Asiatic Society of Bangladesh, Science, 2017)
The present study was carried out to measure the physico-chemical variables of surface water of the Meghna River from September 2015 to March 2016. Air temperature, water temperature, soil pH, water pH, DO, BOD5, COD, TSS, TDS, PO4-P, NO3-N and EC concentrations in water samples were found to range from 14-29°C, 11-28°C, 5.9-6.9, 7.2-7.5, 4.2-6.71 mg/L, 0.67-3.71 mg/L, 2.5-5.9 mg/L, 8-20 mg/L, 72-130 mg/L, 0.11- 0.90 μg/l, 0.115-0.90 μg/l and 115.8-220 μScm-1 respectively. River Pollution Index (RPI) indicated that the water of river at impacted site was less to moderately polluted. Unimpacted site was also less polluted as per RPI and mostly used for agriculture. Correlation Matrix (CM) and Multivariate statistical analyses namely Cluster Analysis (CA), Principal Component Analysis (PCA) and Factors Analysis (FA) indicated that river water was polluted. The principal causes of the pollution of the river were haphazard industrialization, domestic sewage and agricultural inputs. Using of river water can pose serious problems to human health by biological food chain. This research suggests to proper management of the river with eco-friendly industrialization and urbanization for sustainable development of the country. Asiat. Soc. Bangladesh, Sci. 43(1): 23-35, June 2017